1999
DOI: 10.1159/000051222
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Characterisation of Frontotemporal Dementia on Chromosome 3

Abstract: We have previously localized a locus causing familial nonspecific dementia to the centromeric region of chromosome 3 in a pedigree from the Jutland area of Denmark. This pedigree shows anticipation. Here we present further analysis of these anticipation data which are suggestive of trinucleotide repeat expansion involvement. We also outline our strategies to clone the mutant gene via its putative associated trinucleotide repeat sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 35 publications
1
28
0
1
Order By: Relevance
“…Existing data suggest that enhanced apoptosis appears in the progression of CKD and uremic milieu per se is partly responsible for the phenomenon [1,2,3,9,10]. We demonstrated that expression of Bcl-2 decreased significantly in the course of CKD which remained the only independent predictor.…”
Section: Discussionmentioning
confidence: 51%
“…Existing data suggest that enhanced apoptosis appears in the progression of CKD and uremic milieu per se is partly responsible for the phenomenon [1,2,3,9,10]. We demonstrated that expression of Bcl-2 decreased significantly in the course of CKD which remained the only independent predictor.…”
Section: Discussionmentioning
confidence: 51%
“…DNA ladders are produced by cleavage of genomic DNA between nucleosomes to generate fragments with lengths corresponding to multiple integers of approximately 180 bp [33]. These morphologic changes represent the classic hallmarks of apoptosis that are distinct from cell necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cendoroglo et al [33] reported an increased apoptosis level in PMN isolated from healthy controls and treated with uremic plasma. This is in agreement with the study by Sardenberg et al [36], who showed that in PMN from HD and uremic patients apoptosis was increased compared to PMN from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lack of analysis of other apoptotic markers is another limitation of our study, it can be speculated that the source of the cfDNA in our study might be apoptosis because of the size of genomic DNA sequences studied. Recent studies suggest that the state of uremia is associated with accelerated apoptosis of lymphocytes, monocytes and neutrophils [17,18,19,20]. Furthermore, caspase-dependent apoptosis of mononuclear cells, neutrophils and mesothelial cells induced by conventional glucose-containing PD solutions with a high glucose degradation product content have been reported [21,22,23,24].…”
Section: Discussionmentioning
confidence: 99%